Spared access to idiomatic and literal meanings: a single-case approach - Razuk, Renata de Oliveira (Palimpsesto - Revista do Programa de Pós-Graduação em Letras da UERJ, 2018)
Resenha do estudo: HILLERT, Dieter Gilberto. “Spared access to idiomatic and literal meanings: a single-case approach”. Brain and Language. Amsterdam: Elsevier Science Publisher, v. 89, 2004, p. 207-215.